Jet and torus orientations in high redshift radio galaxies - Drouart, G.; De Breuck, C.; Vernet, J.; Laing, R.; Seymour, Nick; Stern, D.; Haas, M.; Pier, E.; Rocca-Volmerange, B. (2012)
We examine the relative orientation of radio jets and dusty tori surrounding the active galactic nucleus (AGN) in powerful radio galaxies at z > 1. The radio core dominance R = Pcore 20GHz/P extended 500MHz serves as an orientation indicator, measuring the ratio between the anisotropic Doppler-beamed core emission and the isotropic lobe emission. Assuming a fixed cylindrical geometry for the hot, dusty torus, we derive its inclination i by fitting optically-thick radiative transfer models to spectral energy distributions obtained with the Spitzer Space Telescope. We find a highly significant anti-correlation (p < 0.0001) between R and i in our sample of 35 type 2 AGN combined with a sample of 18 z ~ 1 3CR sources containing both type 1 and 2 AGN. This analysis provides observational evidence both for the Unified scheme of AGN and for the common assumption that radio jets are in general perpendicular to the plane of the torus. The use of inclinations derived from mid-infrared photometry breaks several degeneracies which have been problematic in earlier analyses. We illustrate this by deriving the core Lorentz factor G from the R-i anti-correlation, Γ ≳ 1.3.